2009
DOI: 10.1016/s1570-7946(09)70710-2
|View full text |Cite
|
Sign up to set email alerts
|

Pareto Optimization of an Industrial Ecosystem: Sustainability Maximization

Abstract: -This work investigates a procedure to design an Industrial Ecosystem for sequestrating CO 2 and consuming glycerol in a Chemical Complex with 15 integrated processes. The Complex is responsible for the production of methanol, ethylene oxide, ammonia, urea, dimethyl carbonate, ethylene glycol, glycerol carbonate, β-carotene, 1,2-propanediol and olefins, and is simulated using UNISIM Design (Honeywell). The process environmental impact (EI) is calculated using the Waste Reduction Algorithm, while Profit (P) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2014
2014
2015
2015

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
0
5
0
3
Order By: Relevance
“…With this approach, Monteiro et al [19] employed Pareto optimization of a biorefinery of microalgal biomass aiming at maximizing sustainability, as a dual objective problem: minimizing environmental impact while maximizing economic performance. Social metrics were neglected both due to lack of recognized indicators and to the georeferencing nature of such quantification.…”
Section: Sustainability Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…With this approach, Monteiro et al [19] employed Pareto optimization of a biorefinery of microalgal biomass aiming at maximizing sustainability, as a dual objective problem: minimizing environmental impact while maximizing economic performance. Social metrics were neglected both due to lack of recognized indicators and to the georeferencing nature of such quantification.…”
Section: Sustainability Metricsmentioning
confidence: 99%
“…Social metrics were neglected both due to lack of recognized indicators and to the georeferencing nature of such quantification. Monteiro et al [19] proposed a superstructure for a biorefinery and concluded that increasing the weight of environmental objectives against economic performance makes unattractive some sectors of the biorefinery.…”
Section: Sustainability Metricsmentioning
confidence: 99%
“…To illustrate the potential industrial application of microalgae, Figure 19 shows a schematic of microalgae bioconversion of CO 2 and its downstream processing in a biorefinery arrangement producing long-chain fatty acids (PUFA´s, MUFA´s and PUFA´s), biodiesel, green diesel, gasoline, biogas, urea, N 2 and propylene carbonate. Monteiro et al (2010) employed Pareto optimization of what was named an "industrial ecosystem" comprised of a biorefinery of microalgal biomass aiming at maximizing sustainability of the productive arrangement. The authors concluded that increasing the weight of environmental objectives against economic performance might make sectors of the proposed original superstructure of amenable processes unattractive.…”
Section: Biochemical Conversion Of Comentioning
confidence: 99%
“…Identification of social enabling factors for EIPs Cao et al [23], Kim et al [34], Gu et al [35], Maillé & Fraillet [36], Schulze, [37], Monteiro et al, [38] Simulation / Optimization Agent-based simulation of a hypothetical EIP; mixed-integer programming for generating EIP configurations…”
Section: Introductionmentioning
confidence: 99%